2021
DOI: 10.3389/fonc.2021.622827
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model Based on Deep Convolutional Neural Network Improves Diagnostic Accuracy of Intramucosal Gastric Cancer (With Video)

Abstract: Background and AimsPrediction of intramucosal gastric cancer (GC) is a big challenge. It is not clear whether artificial intelligence could assist endoscopists in the diagnosis.MethodsA deep convolutional neural networks (DCNN) model was developed via retrospectively collected 3407 endoscopic images from 666 gastric cancer patients from two Endoscopy Centers (training dataset). The DCNN model’s performance was tested with 228 images from 62 independent patients (testing dataset). The endoscopists evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Tang et al. ( 16 ) developed a D-CNN model to predict gastric mucosal cancer using 3407 gastroscopic images from 666 gastric cancer patients as the training set and 228 gastroscopic images as the test set. The AUC of the AI model for distinguishing intramucosal cancer from advanced gastric cancer was found to be 0.942, with a sensitivity of 0.905 and a specificity of 0.853.Zhu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al. ( 16 ) developed a D-CNN model to predict gastric mucosal cancer using 3407 gastroscopic images from 666 gastric cancer patients as the training set and 228 gastroscopic images as the test set. The AUC of the AI model for distinguishing intramucosal cancer from advanced gastric cancer was found to be 0.942, with a sensitivity of 0.905 and a specificity of 0.853.Zhu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al reported that the CADx system showed an accuracy of 88.2%, a sensitivity of 90.5%, and a specificity of 85.3% for differentiating mucosal/submucosal invasion in WLI images. They also reported that the diagnostic performance of endoscopists improved by using a CADx system not only in novice endoscopists (accuracy 74.0% vs. 84.6%, p < 0.001; sensitivity 81.1% vs. 85.7%, p = 0.018; specificity 65.2% vs. 83.3%, p < 0.001) but also in expert endoscopists (accuracy 79.8% vs. 85.5%, p < 0.001; sensitivity 84.3% vs. 87.4%, p = 0.018; specificity 74.2% vs. 83.0%, p < 0.001) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning approaches started to improve medical care and biomedical research in recent years. It has been used in fields such as radiology, telehealth, clinical care, and even stem cell biology [20,[31][32][33].…”
Section: Microscopic Preservation Of Cardiac Ecmmentioning
confidence: 99%